Oxygen Delivery and Oxygen Consumption in Pediatric Fluid Refractory Septic Shock During the First 42 h of Therapy and Their Relationship to 28-Day Outcome - Goonasekera, Chulananda D. A.; Carcillo, Joseph A.; Deep, Akash (Frontiers in Pediatrics, 2018)
Background In septic shock, oxygen delivery (DO2) and oxygen consumption (VO2) are dysfunctional. The current therapeutic regimens are geared to normalize global oxygen delivery (DO2) via goal directed therapies but mortality remains high at 10-20%. Methods We studied cardiac index (CI), systemic vascular resistance index (SVRI), central venous oxygen saturation (ScvO2), central venous pressure (CVP), peripheral oxygen saturation (SpO2), mean blood pressure (MBP), body temperature, blood lactate, base excess and hemoglobin concentration (Hb) in a cohort of children admitted in 'fluid-refractory' severe septic shock to pediatric intensive care, over 4.5-years. We calculated their 6 hourly global oxygen delivery (DO2) and global oxygen consumption (VO2) over the first 42 hours and looked at factors associated with VO2/DO2 ratio (i.e. global oxygen extraction, gO2ER) and 28-day mortality. Results Sixty-two children mean age (SD) 7.19 (5.44) years were studied. Fifty-seven (93%) children were sedated and mechanically ventilated and all received adrenaline or noradrenaline or both and added milrinone in 6 (9.6%). At 28 days, 9 (14.5%) were dead. The global oxygen extraction ratio (gO2ER) was consistently lower amongst the survivors and independently predicted mortality (ROC AUC =0.75). A lactate level of 4mmol/l or above, when associated with a concurrent metabolic acidosis predicted mortality with a sensitivity of 100% (95% CI 90.5 – 100) and a specificity of 67.7% (95% CI 62.2 – 72.9). A gO2ER of 0.48 or above on admission to the PICU was associated with death with a 66.7% sensitivity (95%CI 29.9-92.5) and 90.5% specificity (95%CI 79.3-96.8). A global O2ER of >0.48 combined with a concurrent blood lactate >4.0 mmol/l at any time within the first 42 hours of therapy predicted death with a sensitivity of 63.9% (95% CI, 46.2 – 79.1) and specificity of 97.8% (95% CI, 95.7 – 99.0). A radar plot identified MBP-CVP difference, and CI as additional goals of therapy that may offer a survival benefit. Conclusions Global O2ER of >0.48 with a concurrent blood lactate >4.0 mmol/l in children with metabolic acidosis was an independent factor associated with death. Trends of gO2ER seem useful to recognize survivors and non-survivors early in the illness.